Lselectin Levels in Patients with Endometriosis - Melkiandri Fanggidae; Maria F.T. Loho; Maya E. Mewengkang (Indonesian Journal of Obstetrics and Gynecology, 2018)
Objective: To investigate the L-selectin profile in endometrioticpatients.Methods: This was a cross-sectional study. Subjects were patientsdiagnosed endometriosis based on clinical examination, transvaginalultrasound, MRI and CT scan at the Department of Obstetricsand Gynecology of Prof. Dr. R.D. Kandou Hospital Manado, SiloamHospital and Network Hospital starting from January 2017 to May2017. The blood samples in patients prior to surgery were taken ona vein and then separated to obtain serum. Further more, serumlevels of L-selectin were measured using enzyme-linked immunosorbentassay (ELISA). Data were analyzed with SPSS version 22.0to see significance level.Results: Of the 18 samples, based on age, endometriosis highest inthe group > 26 years ie 17 patients (94.44%), followed by the agegroup of 21-25 years in 1 patient (5:56%), and none of thepatients in the age group <20 years (0%). Based on parity, themost established on a parity group 0 for 11 patients (61.11%),followed by the 1-3 parity group of 7 patients (38.99%), and nopatients in the parity > 4 (0%). Based on the highest stage is thethird stage as many as 11 people (61.11%), followed by stage 4 of7 patients (38.99%), and none of the patients in stage 1 or stage 2(0%). From a statistical test used to stage endometriosis age, theT test, p value 0.286. From a statistical test according to the levelsof L-selectin on endometriosis stadium used, the T test, p value0.090. Results of correlation tests were used, namely statingPearson test p value of 0.921.Conclusion: L-selectin levels in women with endometriosisincreased according to clinical stage, but not significant in statisticaltests. There is no significant relationship between age withstages or levels of L-selectin in women with endometriosis.Keywords: adhesion, age, endometriosis, L-selectin, stage